1981
DOI: 10.1021/ma50002a003
|View full text |Cite
|
Sign up to set email alerts
|

Rare earth metal containing polymers. 3. Characterization of ion-containing polymer structures using rare earth metal fluorescence probes

Abstract: Eu3+, Tb3+, and Co2+ salts of polymers containing carboxylic acid and sulfonic acid ligands were prepared and characterized. The polymers investigated were poly(acrylic acid) (PAA), copolymers of styrene-acrylic acid (PSAA), styrene-maleic acid (PSM), and methyl methacrylate-methacrylic acid (PMM/MA), and partially carboxylated and sulfonated polystyrenes (CPS and SPS). The lanthanide salts of these polymers showed characteristic lanthanide ion fluorescence in the solid state on excitation with UV light. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
51
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(53 citation statements)
references
References 4 publications
1
51
1
Order By: Relevance
“…The chemical attachment method consists of two parts: (Ⅰ) the interaction of rare earth ion with linear functionalized(such as carboxyl-containing) polymers; (Ⅱ) the polymerization and copolymerization of rare earth monomers. Okamoto had produced a lot of rare earth containing polymers through method (Ⅰ) as the first time in 1980 [8]. They found that the fluorescence intensities of the rare earth containing polymers were increase linearly with the rare earth ion content.…”
Section: .Introductionmentioning
confidence: 99%
“…The chemical attachment method consists of two parts: (Ⅰ) the interaction of rare earth ion with linear functionalized(such as carboxyl-containing) polymers; (Ⅱ) the polymerization and copolymerization of rare earth monomers. Okamoto had produced a lot of rare earth containing polymers through method (Ⅰ) as the first time in 1980 [8]. They found that the fluorescence intensities of the rare earth containing polymers were increase linearly with the rare earth ion content.…”
Section: .Introductionmentioning
confidence: 99%
“…6,7 Recently, macromolecular lanthanide complexes (MLnC) are of increasing interest in supermolecular chemistry, biology, and functional materials. 8,9 They are excellent photoluminescent materials being extensively studied as potential molecular and supermolecular devices, 10 fluorescent probes and luminescent labels in chemical, biological systems, and medical diagnostics. 11,12 As a part of our continuing studies on the macromolecular metal complexes, [13][14][15][16][17] we synthesized the luminescent Ln-PSt/BAME (Ln ¼ Y, Sm, Dy, Eu and Tb; St ¼ styrene; BAME ¼ 2-butenedioic acid (z)-mono-ethyl ester) complexes, and a detailed research on the structure and characterization for both the copolymers and the Ln-PSt/BAME complexes had been performed.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicated that the radiolysis caused chain degradation of PEO and produced carbonyl group (aldehyde moiety) at the end of the cleaved polymer chain. The chromophore moiety produced transfer the energy to the Tb3+ ion sited within the non-radiative energy transfer distance (14). The Tb-fluorescence sensitizing technique is effective in detecting such dilute species in PEO.…”
Section: Introductionmentioning
confidence: 99%